1997
DOI: 10.1017/s0317167100033011
|View full text |Cite
|
Sign up to set email alerts
|

Motor Evoked Potentials and Disability in Secondary Progressive Multiple Sclerosis

Abstract: Background: To investigate the mechanisms underlying disability in multiple sclerosis (MS), 40 patients with the relapsing-remitting form of the disease and 13 patients with secondary progressive MS underwent multimodal evoked potential (EP), motor evoked potential (MEP), and spinal motor conduction time evaluation. Clinical disability was evaluated by the expanded disability status scale (EDSS) and functional system scales. In secondary progressive MS patients, magnetic resonance imaging (MRI) was used to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Confirming previous reports [9], our patients' CMCT values correlated significantly with their EDSS scores. CMCT could therefore be considered a neurophysiological marker of disease and also a reliable measure for quantifying the involvement of central motor pathways and clinical deficits.…”
Section: Discussionsupporting
confidence: 92%
“…Confirming previous reports [9], our patients' CMCT values correlated significantly with their EDSS scores. CMCT could therefore be considered a neurophysiological marker of disease and also a reliable measure for quantifying the involvement of central motor pathways and clinical deficits.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, a correlation between central motor conduction time and the maximum force of phasic muscle contraction in MS has been described [29]; however, a correlation was not observed with finer measures of hand dexterity (Purdue pegboard or tapping frequency). Likewise, the EDSS and a pyramidal functional system score have been shown to correlate with central motor conduction times and transcallosal inhibition in relapsing-remitting and secondary progressive MS [9,23]. In the present study, we have shown that not only corticomotor conduction, but motor threshold and MEP amplitude, are correlated with the EDSS and a dexterity task, supporting the accepted notion that the degree of conduction block in the corticospinal tract has a major role in motor disability in MS.…”
Section: Discussionsupporting
confidence: 87%
“…They reported a marked increase in CMCT in the group with progressive MS (SPMS and PPMS combined), independent of disease duration, number of spinal lesions or clinical motor deficit. Facchetti et al, (1997) also demonstrated a significant increase in CMCT, correlating with EDSS and pyramidal Functional System score, as well as a higher incidence of abnormal SSEP, MEP and BAEP in patients with SPMS when compared to those with RRMS and to healthy controls.…”
Section: Tms In the Classification Of Ms Subtypementioning
confidence: 81%